Safety and efficacy study of oral metronomic capecitabine combined with pyrotinib in HER2-positive metastatic breast cancer: A phase II trial - Maiyue He; Jiaxuan Liu; Zijing Wang; Fei Ma; Jiayu Wang; Pin Zhang; Qing Li; Peng Yuan; Yang Luo; Ying Fan; Hongnan Mo; Bo Lan; et al. (Breast, 2023)
Purpose: To analyze the safety and efficacy of orally administered metronomic capecitabine plus pyrotinib in HER2 positive metastatic breast cancer (MBC) patients, we conducted a prospective phase II study with a single-arm design. Methods: HER2 positive patients received oral metronomic capecitabine 500 mg three times a day and pyrotinib 400 mg per day. The primary endpoint was progression-free survival (PFS). Other endpoints included objective response rate (ORR), overall survival (OS), clinical benefit rate (CBR) and safety. Results: The study included 50 patients with MBC that was HER2-positive, while 1 patient was excluded due to nonstandard medication. The median PFS and OS was 11.9 months (95%CI 8.8–14.6) and 29.3 months (95%CI 24.4–34.8) respectively. ORR was 34.7%, and CBR was 81.6% with 2 CR (4.1%), 15 PR (30.6%) and 23 SD (46.9%). The mPFS in first- or second-line treatment was 12.2 months. The most frequent treatment-related adverse events included hand-foot syndrome, diarrhea, vomiting and nausea. Grade 3 adverse events occurred in 15(30.6%) patients, including hand-foot syndrome (12.2%), diarrhea (12.2%), vomiting (4.1%), and nausea (2.0%). 1 grade 4 adverse event of diarrhea (2.0%) was observed. Conclusion: The combination of metronomic capecitabine and pyrotinib is a promising regimen with competitive efficacy and improved tolerability in HER2 positive metastatic breast cancer patients.